Blockchain-based tokens issuance under the EU framework: is it underdeveloped? - Dikanskis, Dmitrijs (Riga Graduate School of Law, 2020)
This thesis aims to explore a theoretical background for blockchain-based funding options and token issuance, to verify tokens classification from the legal point of view based on their structure and method of distribution, to analyse legal perimeter of token issuance in the EU for inconsistencies and to compare with the US regulation which is regarded as one of the better enforced in the world, and to discuss further regulatory responses. The findings are that despite the classification of tokens (utility and security) is established and the legal perimeter is defined, more certainty on classification and definitions are still recommended. The substantial convergence between the EU and the US securities regulation regimes shows that the EU legal framework covers similarly the essential areas of token offerings, although the definitions applied in both jurisdictions are different (‘transferable securities’ and ‘investment contract’). The research suggests that the EU regulators and policymakers may respond to the future technological advances and market preferences towards a new mode of funding using 'soft law' measures, establishing sandboxes or creating the bespoke regime for crypto-assets. However, the author promotes utilising blockchain technology abilities and its code-driven nature for better compliance and regulatory measures.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Blockchain